SOFT SKILLS PENDIDIKAN DALAM PENDIDIKAN ISLAM - Sulham Efendi Hasibuan; Nurjulianti Nurjulianti; Fifi Angraini; Riska Romadhona (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Islamic education holds a crucial role in shaping well-rounded individuals, not only intellectually but also emotionally and socially. This paper explores the urgency of soft skills development within the framework of Islamic education, particularly in the context of Islamic Religious Education (IRE). Employing a descriptive qualitative method through literature review, the author examines recent scholarly sources that discuss the integration of Islamic values with the enhancement of interpersonal abilities such as communication, collaboration, and leadership. The findings reveal that Islamic education has significant potential to cultivate soft skills by internalizing moral values, ethical conduct, and the practical application of Islamic teachings in daily life. The study suggests that when Islamic education broadens its focus beyond cognitive and doctrinal content to include interpersonal skill development, it can produce resilient Muslim individuals with strong character who are capable of facing global challenges. The conclusion highlights that fostering soft skills is an essential component of holistic Islamic education and aligns with the demands of contemporary society. ABSTRAK Pendidikan Islam berperan penting dalam membentuk individu yang seimbang, tidak hanya dari sisi intelektual, tetapi juga dalam aspek emosional dan sosial. Tulisan ini membahas urgensi pengembangan soft skills dalam pendidikan Islam, khususnya dalam proses pembelajaran Pendidikan Agama Islam (PAI). Dengan menggunakan pendekatan deskriptif kualitatif melalui studi kepustakaan, penulis mengulas literatur-literatur mutakhir yang membahas keterpaduan nilai-nilai Islam dengan penguatan keterampilan interpersonal seperti komunikasi, kerja sama, dan kepemimpinan. Hasil analisis menunjukkan bahwa pendidikan Islam sangat potensial dalam menanamkan soft skills melalui pembiasaan nilai-nilai moral, etika, dan implementasi ajaran Islam dalam aktivitas sehari-hari. Temuan ini mengungkapkan bahwa apabila pendidikan Islam tidak hanya menitikberatkan pada aspek intelektual dan keagamaan, tetapi juga memberi perhatian pada pengembangan keterampilan sosial, maka akan terbentuk generasi Muslim yang tangguh, memiliki karakter unggul, dan siap bersaing di era global. Kesimpulan dari artikel ini menegaskan bahwa pembinaan soft skills adalah bagian yang tak terpisahkan dari konsep pendidikan Islam yang menyeluruh dan sesuai dengan tantangan zaman kini.